Immunological Efficacy of Vaccination against COVID-19 in Employees of Medical Institutions of Various Profiles: Psychiatric Hospital and Regional Hospital - A. A. Murzina; A. V. Zubkov; O. A. Svitich; A. N. Kaira (Эпидемиология и вакцинопрофилактика)
Relevance. On the territory of the Russian Federation, mass vaccination of the population is recognized as a priority health strategy against COVID-19, Gam-COVID-Vac vaccine has been widely used. The main risk group, which is subject to priority vaccination, are employees of medical organizations (MO). The determination of IgG to SARS-CoV-2 is an important parameter for assessing the intensity and duration of post-vaccination immunityAims. Study the immunological efficacy of the vaccine Gam-COVID-Vac used by employees of a psychiatric hospital and a regional hospital.Materials and methods. A study of the blood sera of 410 employees of two MO of various profiles who received one full course of the Gam-COVID-Vac» vaccine for the presence of IgG to RBD Spike SARS-CoV-2 using a set of reagents «SARS-CoV-2-IgG quantitative-ELISA-BEST» and IgG to NC SARS-CoV-2 using a set of reagents «ELISA anti-SARS-CoV-2 IgG».Results and discussion. Specific IgG to RBD Spike SARS-CoV-2 after vaccination with «Gam-COVIDVac » were found in 92.9% of psychiatric hospital staff and 98.0% of the regional hospital. Antibodies of class G to SARS-CoV-2 with a level of 300 BAU/ml or more were detected in 11.6% of psychiatric hospital staff and in 70.0% of regional hospitals, which is associated with the smallest proportion of persons in a psychiatric hospital with hybrid immunity than in a regional hospital (67.4% vs. 89.0%, respectively). A study of employees of the Ministry of Defense of various profiles revealed a difference in the level of IgG to RBD Spike SARS-CoV-2: 178.0 BAU/ml in a psychiatric hospital and 366.0 BAU/ml in a regional hospital. In a psychiatric hospital, the IgG level was highest up to 3 months after the completed vaccination – 166.4 BAU/ml, in a regional hospital from 3 to 6 months – 362.8 BAU/ml, then the number of antibodies decreases, which indicates the importance of monitoring for class G antibodies to SARS-CoV-2 at different times after vaccinations. Among the employees of the two MO, mild forms of the COVID-19 disease prevailed.Conclusion. Thus, the high immunological effectiveness of vaccination against COVID-19 with Gam-COVID-Vac was established in a group of employees of two MO, and the need for serological monitoring for the purpose of revaccination was also shown.